1989
DOI: 10.1126/science.2466335
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Leukocyte Adhesion Molecule 1: an Inducible Receptor for Neutrophils Related to Complement Regulatory Proteins and Lectins

Abstract: Focal adhesion of leukocytes to the blood vessel lining is a key step in inflammation and certain vascular disease processes. Endothelial leukocyte adhesion molecule-1 (ELAM-1), a cell surface glycoprotein expressed by cytokine-activated endothelium, mediates the adhesion of blood neutrophils. A full-length complementary DNA (cDNA) for ELAM-1 has now been isolated by transient expression in COS cells. Cells transfected with the ELAM-1 clone express a surface structure recognized by two ELAM-1 specific monoclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
815
2
9

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,890 publications
(859 citation statements)
references
References 53 publications
29
815
2
9
Order By: Relevance
“…E-selectin was later found to mediate leukocyte adhesion to endothelial cells and their subsequent penetration of the vascular wall. 11 It is now clear that inflammatory factors affect BP by inducing the expression of adhesion molecules, mainly E-selectin, in endothelial tissue. Generally, E-selectin induces the adhesion and aggregation of leukocytes, which subsequently migrate into the vascular wall or extravascular space, thus injuring vascular endothelial cells, impairing endothelium-dependent vascular relaxation and finally leading to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…E-selectin was later found to mediate leukocyte adhesion to endothelial cells and their subsequent penetration of the vascular wall. 11 It is now clear that inflammatory factors affect BP by inducing the expression of adhesion molecules, mainly E-selectin, in endothelial tissue. Generally, E-selectin induces the adhesion and aggregation of leukocytes, which subsequently migrate into the vascular wall or extravascular space, thus injuring vascular endothelial cells, impairing endothelium-dependent vascular relaxation and finally leading to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…4 A). A rapid, but transient increase in AICL mRNA was found between 1 and 8 h after stimulation with a maximal induction at 3 h. Although the induction of AICL mRNA is probably less pronounced, transcription kinetics of AICL are similar to CD69 Lopez-Cabrera et al 1993;Ziegler et al 1994) and other rapidly upregulated antigens such as tissue factor, CD62E, and CD97 (Scarpati and Sadler 1989;Bevilacqua et al 1989;Hamann et al 1995). The rapid mRNA turnover of these antigens is regulated by a fast degradation of the highly unstable mRNAs (Santis et al 1995).…”
Section: Transcription Of Aicl Is Transiently Upregulated During Lympmentioning
confidence: 99%
“…In contrast to the vast majority of other adhesion molecules, the selectins mediate cell contact via binding to carbohydrate ligand structure and thus, they are lectins. L-selectin is found on most types of leukocytes (Finger et al, 1996), E-selectin is specific of endothelial cells (Bevilacqua et al, 1989) and P-selectin is found on endothelium and platelets (McEver et al, 1989).…”
Section: Molecular Mechanisms That Control Leukocyte Extravasationmentioning
confidence: 99%